Chemical capacitance proposed for manganite-based ceramics - Molak, A. (Condensed Matter Physics, 2013)
The measured value of effective electric permittivity ϵeff of several compounds, e.g., (BiNa)(MnNb)O₃, (BiPb)(MnNb)O₃, and BiMnO₃ increases from a value ≅10÷100 at the low temperature range (100÷300 K) up to the high value reaching the value 10⁵ at high temperature range, e.g., 500÷800 K. Such features suggest the manifestation of thermally activated space charge carriers, which effect the measured capacitance. The measured high-value effective permittivity of several manganite compounds can be ascribed to the chemical capacitance Cμ=e² ∂Ni/∂μi expressed in terms of the chemical potential μ. The chemical capacitance Cμ(cb)=e² nC/kBT depends on temperature when the conduction electrons with density nC=NCexp(μn-EC)/kBT are considered. The experimental results obtained for the manganite compounds, at high temperature range, are discussed in the framework of the chemical capacitance model. However, the measured capacitance dependence on geometrical factors is analysed for BiMnO3 indicating that the non-homogeneous electrostatic capacitor model is valid in 300÷500 K range.